THE EFFECT OF THE PRODUCT DEVELOPMENT PROCESS IN IMPROVING PRODUCT QUALITY CNC TECHNOLOGY IS AN İNTERACTIVE VARIABLE-AN EXPLORATORY STUDY IN IBN MAJID GENERAL COMPANY - Noor Adil Sekhi Al-sadoon; Prof. Dr. Hashim Nayef Hashim Al-Hachim (American Journals Publishing, 2024)
The research aims to reveal the relationship between the product development process as an independent variable and CNC technology as an interactive variable to improve product quality as a dependent variable. The research problem was represented in a main question (What is the effect of the product development process in improving product quality? CNC technology as an interactive variable)?The importance of the research lies in its focus on the product development process and the necessity of using modern production methods such as CNC technology because of its important role in achieving the economic development of the country. Finally, the research reached a set of conclusions, the most important of which is that support from senior management is a basic and important element for improving the quality of products. By keeping pace with technologies, technological developments and digital machines, providing training programs to raise the level of capabilities and skills they possess, and creating working people with experience and competence to ensure the survival and growth of the company, as well as revealing the presence of acceptable levels of the dimensions of the product development process in the company, the research sample, and at an acceptable level so attention must be paid to them Increasingly to improve the quality of future products.
Keywords: Product development process, improving product quality, CNC technology.